2022
DOI: 10.1038/s41598-022-06208-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the invasive bird-parasitic fly Philornis downsi over the host interbreeding period in the Galapagos Islands

Abstract: Many parasites of seasonally available hosts must persist through times of the year when hosts are unavailable. In tropical environments, host availability is often linked to rainfall, and adaptations of parasites to dry periods remain understudied. The bird-parasitic fly Philornis downsi has invaded the Galapagos Islands and is causing high mortality of Darwin’s finches and other bird species, and the mechanisms by which it was able to invade the islands are of great interest to conservationists. In the dry l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…To assess changes in genetic structure across the sampling period, all specimens collected from nests and traps were analysed (1) for all years pooled, and (2) separately per year (2006,2008,2014,2020), and for each of the 10% and 30% missingness datasets. Samples from a given year are independent generations as previous studies found that P. downsi only survives to the next year's breeding season, but not subsequent breeding seasons, and our sampling periods are 2-6 years apart (Causton et al 2019;Bulgarella et al 2022).…”
Section: Genetic Variation and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…To assess changes in genetic structure across the sampling period, all specimens collected from nests and traps were analysed (1) for all years pooled, and (2) separately per year (2006,2008,2014,2020), and for each of the 10% and 30% missingness datasets. Samples from a given year are independent generations as previous studies found that P. downsi only survives to the next year's breeding season, but not subsequent breeding seasons, and our sampling periods are 2-6 years apart (Causton et al 2019;Bulgarella et al 2022).…”
Section: Genetic Variation and Structurementioning
confidence: 99%
“…However, increased multiple mating can decrease female longevity in insects, due to the increased cost of both mating and egg production (Arnqvist and Nilsson 2000;Kawagoe et al 2001;Gotoh and Tsuchiya 2008). Given that females must survive during the arid, non-breeding period on the Galápagos (Causton et al 2019;Bulgarella et al 2022), selection for increased female longevity may be driving the observed decrease in multiple mating. The costs and benefits of polyandry in P. downsi are currently not understood.…”
Section: Shifts In Reproductive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The fly larvae then hatch and feed on the blood of developing chicks, causing high mortality across bird species ( Fessl et al 2018 ). Since the ramifications of this invasion have been realized, greater attempts have been made to study the population dynamics, ecology, and natural history of this species in its native and introduced range with the hope that these insights can inform more effective control ( Bulgarella et al 2015 , 2022 , Kleindorfer and Dudaniec 2016 , Kleindorfer et al 2016 , Knutie et al 2016 , Causton et al 2019 , Cimadom et al 2019 , Common et al 2021 , Pike et al 2021 ). While much progress has been made in understanding P. downsi , there are still substantial gaps in our knowledge of this species basic ecology and reproductive behavior ( Fessl et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%